2009
DOI: 10.22459/ta31.12.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Early Prehistory of Fiji

Abstract: terra australis 31Terra Australis reports the results of archaeological and related research within the south and east of Asia, though mainly Australia, New Guinea and island Melanesia -lands that remained terra australis incognita to generations of prehistorians. Its subject is the settlement of the diverse environments in this isolated quarter of the globe by peoples who have maintained their discrete and traditional ways of life into the recent recorded or remembered past and at times into the observable pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
(189 reference statements)
0
2
0
Order By: Relevance
“…The past three decades of zooarchaeological investigation of Lapita sites have revealed that Lapita fishing was mainly practised in inshore coral-reef environments, especially during the first era of migration about 3300 to 2800 BP (cf. Butler 1988Butler , 1994Clark and Szabó 2009;Green 1979Green , 1986Kirch 1988Kirch , 1997Kirch , 2000Kirch and Dye 1979;Kirch and Yen 1982;Summerhayes et al 2010). Yet direct and indirect evidence suggests that Lapita people exploited both near-shore and off-shore marine environments, using a variety of fishing methods including angling, trolling, netting, poison, spears and traps (Butler 1994;Green 1986;Kirch 1997Kirch , 2000Ono 2003;Walter 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The past three decades of zooarchaeological investigation of Lapita sites have revealed that Lapita fishing was mainly practised in inshore coral-reef environments, especially during the first era of migration about 3300 to 2800 BP (cf. Butler 1988Butler , 1994Clark and Szabó 2009;Green 1979Green , 1986Kirch 1988Kirch , 1997Kirch , 2000Kirch and Dye 1979;Kirch and Yen 1982;Summerhayes et al 2010). Yet direct and indirect evidence suggests that Lapita people exploited both near-shore and off-shore marine environments, using a variety of fishing methods including angling, trolling, netting, poison, spears and traps (Butler 1994;Green 1986;Kirch 1997Kirch , 2000Ono 2003;Walter 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In every archipelago, a number of ambitious research programs were initiated in the 1990s (e.g. Bedford et al 1999;Clark and Anderson 2009;Sand 1996;Sheppard et al 2000;Summerhayes 2000) and carried on in the following decades, allowing us to broaden, sometimes exponentially, our knowledge of the long past of this part of Oceania. Sadly, in a period characterised by important economic development in the region with the construction of numerous international hotels and tourism-related facilities, new roads and airstrips, extensions of townships, factories and housing, and logging and mining, very few large-scale archaeological rescue excavations in the form of cultural resource management (CRM) programs have been carried out.…”
Section: Introductionmentioning
confidence: 99%